1972
DOI: 10.1111/j.1476-5381.1972.tb09578.x
|View full text |Cite
|
Sign up to set email alerts
|

Some evidence of the active uptake of noradrenaline in the guinea‐pig isolated trachea

Abstract: Summary . Guinea‐pig isolated trachea immersed in a low concentration (50 nm) of (—)‐3H‐noradrenaline accumulates radioactive material against an apparent concentration gradient. . Compartmental analysis based on the decay curve of radioactive material content during washout and its comparison with that of 14C‐sorbitol shows that some extracellular noradrenaline is adsorbed. A considerable mass exists in a slowly exchanging compartment, i.e. is retained. This retention is inversely concentration dependent. . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1973
1973
1990
1990

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…The amine accumulated under these conditions is, to a large extent, located in the cytoplasm Mechanism of noradrenaline eflux (Hamberger et al, 1964;Hamberger, 1967) although a small amount of reserpineresistant binding of noradrenaline occurs (Stitzel & Lundborg, 1967 Lindmar & Muscholl, 1971 ;Foster & O'Donnell, 1972;Starke, 1972). These workers reported that efflux could be resolved into two or three compartments.…”
Section: Discussionmentioning
confidence: 99%
“…The amine accumulated under these conditions is, to a large extent, located in the cytoplasm Mechanism of noradrenaline eflux (Hamberger et al, 1964;Hamberger, 1967) although a small amount of reserpineresistant binding of noradrenaline occurs (Stitzel & Lundborg, 1967 Lindmar & Muscholl, 1971 ;Foster & O'Donnell, 1972;Starke, 1972). These workers reported that efflux could be resolved into two or three compartments.…”
Section: Discussionmentioning
confidence: 99%
“…None of the treatments shown in previous publications to inhibit significantly uptake-with-retention of radioactivity has abolished it; a residuum varying from approximately 1O pmol/g (ouabain, Foster & O'Donnell, 1972;and guanethidine, Foster, 1968) to 17 pmol/g (phenoxybenzamine, Foster, 1968) has always remained despite treatment with apparently maximally effective concentrations of inhibitors of uptake. O'Donnell & Saar (1973) have suggested, on the basis of histochemical evidence, that after incubation with a high concentration of noradrenaline the noradrenaline which is bound to cartilage (extraneuronal, extracellular) does not wash away quickly enough to be dissipated in 30 minutes.…”
Section: Discussionmentioning
confidence: 77%
“…The very fast exponential decay (t_ c 0.6 min) probably represents radioactive incubation medium adhering to the tissue on transfer to the first washing tube. The fast phase (tL c 6 min) represents radioactive material in the interstitial space of the tissue and the slow one (t_ c 120 min) 'cellular' radioactivity (Foster & O'Donnell, 1972).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations